Wind turbine fault estimation using sliding mode observer based on Takagi–Sugeno fuzzy model - Mohammed Taouil; Salaheddine Zouirech; Abdelghani El Ougli; Belkassem Tidhaf (International Journal of Renewable Energy Development, 2026)
This paper presents a fault-estimation approach for utility-scale wind turbines that combines Takagi–Sugeno (TS) fuzzy modeling with a sliding-mode observer (SMO). The nonlinear dynamics of the 4.8 MW benchmark turbine are represented by a TS structure, enabling an LMI-based synthesis of a robust TS–SMO. The proposed observer reconstructs both actuator faults affecting generator torque and sensor faults in blade-pitch measurements. MATLAB/Simulink validations under realistic operating conditions (operating-point variations, wind fluctuations, and disturbances) demonstrate accurate tracking and fast, stable fault reconstruction over the complete simulation horizon. Performance is assessed using the Normalized Sum of Squared Errors (NSSE): the reconstructed faults exhibit low NSSE values in the considered fault scenarios, with the blade-pitch sensor fault achieving NSSE =0.087 %. These results indicate reliable fault estimation while maintaining bounded residuals and avoiding drift. The method relies on standard industrial signals and entails modest online computations (matrix operations and a bounded switching term), facilitating integration into existing condition-monitoring and fault-tolerant control architectures. Overall, TS-guided sliding-mode observation is shown to be an effective and robust solution for wind-turbine fault diagnosis under nonlinearities and exogenous perturbations.